Stem cell transplantation: a 10-year single.centre experience - Georgievski, Borche; Stojanoski, Zlate; Genadieva Stavrikj, Sonja; Pivkova Veljanovska, Aleksandra; Ivanovski, Martin; Karanfilski, Oliver; CHevrevska, Lidija; Krstevska Balkanov, Svetlana; Trajkova, Sanja (My University, 2011)
Stem cell transplantation is the treatment of choice for patients with hematological malignant diseases. Aim of this study is to evaluate the results in 10 years experience with this procedure in our center. During a this period we have treated 195 patients with different malignant hematological diseases.107 male, 88 female with median age of 34 years. Allogeneic sibling transplantation were performed in 56 patients, and autologous transplantation in 139 patients. According to diagnose: AML:91 ALL:10 CML:7 CLL:1 MP:1 NHL:20 HD:27 MM:34 AA:2 Ewing sarcoma: 1. Bone marrow was used as a source of stem cells in 28, PBSC in 168 patients. Conditioning regimen consisted chemotherapy with: Bu-Cy2,Bu- Cy-Mel,BEAM, high dose Melphalan, high dose ICE,Flu/Mel. Engraftment was reached on day +12 (10-24). Median value of MNC in BMT was 3,8x10/Kg (2,5-4,5), while in PBSCT MNC was 4,1x10 (2,8-12,0). TRM in allogeneic recipients was 16%, with non-relapse mortality 10%, and in autologous recipients TRM was 3,8% with non-relapse mortality 2,0%. Primary disease was cause of death after transplantation in 40% in allogeneic, and 66% in autologous transplantation. 35% of allogeneic and 28% of autologous transplantation were transplanted in active disease.